An investigation of maximal hand grip strength related to body mass index in healthy Czech children - Martin Šteffl; Jan Chrudimský (Karolinum Press, 2016)
Hand grip strength is one of the most important markers in muscle strength assessment for many reasons. However, its maximal value in kilograms is highly dependent on body size, which may misrepresent results, especially among children. Therefore, correction by body mass index (BMI) can be used as a suitable approach for its objectification. The aims of this study were to create reference values for the grip to BMI ratio and for hand grip strength for children in the Czech Republic. 554 children of both genders, aged from 4 to 14 years, were included in the current study. Reference values were approximated by Tukey's Hinges percentiles calculation method. The percentile charts were created using the Lambda-Mu-Sigma (LMS) method.